Wiki Editors’ Acceptance of Additional Guidance on Talk Pages - Heimbuch, Sven; Bodemer, Daniel (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
One purpose of Wikis like Wikipedia is to collaboratively generate content. During the creation processes controversies between multiple authors might emerge that are further discussed on a Wiki article’s so-called talk page. Research has shown that controversies grounded on opposing points of view and contradictory evidence can be fruitful to trigger individual elaboration processes. But it has also been shown that many Wikis are not necessarily suited to identify relevant discussion contents and thus need additional support to guide users. In an experimental study (N = 181) we implemented on a Wiki talk page (1) visual controversy status highlights as implicit guidance and (2) a collaboration script directing users towards discussions as explicit guidance. We analyzed their user adoption and influence on Wiki activities. Our results show that both experimental additions affect user behaviors and that in particular the visual controversy status highlights are positively adopted by users.